METAFORA PADA LIRIK-LIRIK LAGU DALAM ALBUM NO SOUND WITHOUT SILENCE KARYA THE SCRIPT - GARING, DELSIUS (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT This research is entitled â€œMetaphor in the Song Lyrics of the Album No Sound without Silence by The Scriptâ€. There are two problems to answer in the analysis. First is what are the types of metaphor found in The Script songs No Sound without Silence album. The second one is what the meaning of the song lyrics in The Script Album No Sound without Silence. This study uses descriptive method. The data sources used in this study are the lyrics of the 12 songs by The Script on No Sound without Silence album. This study uses the theory of Leech (1984) and Lakoff and Johnson (1980). The result reveals that there are 40 metaphors found in the Album No Sound without Silence by The Script. It can be categorized into concretive metaphor, humanizing metaphor, animistic metaphor and synesthetic metaphor. Those metaphors are divided into 32 lines of concretive metaphor, 6 lines of humanizing metaphor, 1 line of animistic metaphor and 3 lines of synesthetic metaphor. Concretive metaphor is mostly used in this album. The songwriter uses the metaphor to add some elegance to the song. In addition the messages of each song were shown by the use of metaphor. In analyzing the meaning, LakoffÂ and Johnsonâ€™s theory about target and source was used. Target refers to the idea or principal subject of metaphor while source refer to the thing that has been equalizer. Keywords: Metaphor, Target and Source, No Sound without Silence.